Estimando as preferências do Banco Central sob regras e discrição: um estudo para o Brasil e Peru - Cunha, Danilo Regis da (2012)
Recent research in macroeconomics has shown a great effort to investigate the motivations behind the actions of policymakers, especially about monetary policy, which focuses on the analysis of how the policymaker reacts to changes in relevant economic variables, and the estimation of their preferences on certain variables such as inflation and product. In this work, it was tried to estimate the preferences of the Central Bank of Brazil (BCB) and the Central Reserve Bank of Peru (BCRP) in environments under commitment, where optimization occurs only once, and discretion where optimization occurs periodically, using a New Keynesian macroeconomic model with optimal monetary policy for the two environments. The data was used on a quarterly basis for the post-inflation targeting period, first quarter of 2000 to the fourth quarter of 2011. The results for both countries show that the data are more consistent for the model under commitment and that monetary policy is conducted optimally. The BCRP gives greater weight to inflation, followed by interest rate not to mention the stability of the product, which is consistent with the recent literature of Peru. In the case of BCB, one can see the concern with the interest rate smoothing and the deviation of output relative to potential output. However, both models show that the main objective of the BCB was not inflation stabilization, which differs from the empirical evidence found in recent literature for Brazil.